MEDTRACK: Intelligent Software Model for Medicine Dispenser System - Pasanjaya, Yoangga Achmad Dwi; Irianto, Kurniawan D. (International Journal of Informatics and Computation, 2025)
Patient non-compliance is one of the major challenges in the healthcare sector, particularly for individuals undergoing long-term treatment. To address this issue, this study developed an intelligent medication monitoring system integrated with an automatic tablet dispenser. To construct the application, we utilize the Waterfall method to ensure a structured and systematic development process. In the initial phase, data were collected through interviews with potential users and healthcare professionals to identify problems and user needs. The software was evaluated using the System Usability Scale (SUS), achieving an average score of 83.6, which falls into the Acceptable category. The testing results from users and healthcare professionals indicate that the application is beneficial, easy to use, and has strong potential for further development. By applying the Waterfall approach, the application was systematically developed and successfully addressed user needs based on structured planning from the early stages.